2003
DOI: 10.1080/713743644
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocondensation and hydrosilylation reactions of methylhydridesiloxane with allyl alcohol

Abstract: The reaction of dehydrocondensation of a,o-bis(trimethylsiloxy)methylhydridesiloxane (n % 53) with allyl alcohol at various ratios of initial compounds, in the presence of anhydrous powders like caustic potassium and platinum chlorohydric acid has been investigated. It was established that in the presence of caustic potassium dehydrocondensation reaction takes place and methylsiloxane oligomers with allylic groups in side chain have been obtained. In the presence of platinum chlorohydric acid competetive dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Since the alcohol was also the solvent in the system, to reduce the number of variables, keeping alcohol in excess ensured a more or less consistent environment. Previous research has applied toluene as a solvent, but in our system, aiming at industrial applications, using additional solvents was not preferred 19,21,23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the alcohol was also the solvent in the system, to reduce the number of variables, keeping alcohol in excess ensured a more or less consistent environment. Previous research has applied toluene as a solvent, but in our system, aiming at industrial applications, using additional solvents was not preferred 19,21,23 …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has applied toluene as a solvent, but in our system, aiming at industrial applications, using additional solvents was not preferred. 19,21,23 It is important to note that due to high polarity and hydrophilicity, water usually tends to be present in alcohols.…”
Section: Alcoholysis Of Pmhsmentioning
confidence: 99%
“…This value of activation energy is near with the value of activation energy of the dehydrocondensation reaction of methylhydridesiloxane with allyl alcohol, which is equal to E act % 29.2 kJ/mole. [11] For some synthesized oligomers GPC investigation were carried out and it was shown that oligomers have mono-and bimodal molecular weight distributions, which are changing in wide range: D ¼ 1,654Ä5,65; M n ¼ 1,077Ä4,564 Â 10 . For some synthesized oligomers differential scanning calorimetric investigations were carried out.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Methyl(ethyl)hydridesiloxanes are also often used in dehydrocondensation reactions for obtaining new derivatives, with organacyclosiloxane fragments, thio-and oxyalkyl groups in the side chain. [9][10][11] …”
Section: Introductionmentioning
confidence: 99%
“…A wide range of catalysts including AIBN, which is very common in many free radical polymerization reactions [20]; gold nanoparticles, used as an active catalyst for breaking the double bond of alkene [21]; and other simple catalysts such as pd, pt, Lewis acids (such as AlCl 3 , HfCl 4 , EtAlCl 2 , ZrCl 4 and TiCl 4 ), Rh and Ru are used in hydrosilylation reaction [22][23][24][25][26][27][28][29][30]. Hydrosilylation reaction is very important for preparing silane-based polymers.…”
Section: Introductionmentioning
confidence: 99%